2004
DOI: 10.1159/000074953
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Transcutaneous Bilirubin Measurements in Neonates: A Correlation Study

Abstract: A prospective observational study was conducted on 212 neonates born between 24 and 42 weeks of gestation who required blood sampling to determine total serum bilirubin (TSB) in the first week of life, prior to phototherapy. The transcutaneous bilirubin (TcB) measurements were performed on the infant’s forehead using BiliCheck™ within ±30 min of a blood sample being drawn. There was significant (r = 0.78) correlation between bilirubin levels obtained transcutaneously and those measured in the infant’s blood. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 18 publications
1
10
0
3
Order By: Relevance
“…The BiliCheck TcB meter has been studied extensively, 6,7,9,12,15,16,19 but its usefulness in the Hispanic population became questionable with the publication of a study done in 2000 at Parkland Hospital by Engle et al 19 This study found that there was a poor correlation between TcB measurements and TSB levels in Hispanic neonates. However, because the Engle study included a relatively large percentage of infants with very high TSB levels (Ն15), the usefulness of TcB measurements in the general population of Hispanic, most of whom would have a normal or mildly elevated bilirubin level, remained unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BiliCheck TcB meter has been studied extensively, 6,7,9,12,15,16,19 but its usefulness in the Hispanic population became questionable with the publication of a study done in 2000 at Parkland Hospital by Engle et al 19 This study found that there was a poor correlation between TcB measurements and TSB levels in Hispanic neonates. However, because the Engle study included a relatively large percentage of infants with very high TSB levels (Ն15), the usefulness of TcB measurements in the general population of Hispanic, most of whom would have a normal or mildly elevated bilirubin level, remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The BiliCheck TcB meter has been studied extensively. 6,7,9,12,15,16,19 BiliCheck measures TcB using the entire spectrum of visible light (380 to 760 nm). White light is transmitted through the skin of the neonate and by analysis of the light reflected back from the neonate's skin, an internal microprocessor calculates the amount of bilirubin present in the skin.…”
Section: Tsb Measurementmentioning
confidence: 99%
“…The conclusions are confl icting. According to Nanjundaswamy et al (2004) BiliCheck measurements can accurately predict TSB values lower than 188 μmol/l in a multiracial preterm and term neonatal population 13 . In agreement, Willems et al (2004) reported the BiliCheck as reliable in very preterm infants of gestational age less than 30 weeks 14 .…”
Section: Discussionmentioning
confidence: 99%
“…25 We reported that in a primarily Hispanic population with relatively high TSBs, the BiliCheckt tended to underestimate TSB, particularly in those neonates with the highest TSB values; 13 other investigators have reported similar findings in primarily non-Hispanic populations. 16 Schumacher 12 noted that this device may be very useful as a screening tool, for example, in evaluating all neonates at 24 hours postnatal, when the majority of neonates will have relatively low TSB. However, he concluded that it may be less useful in neonates with relatively high TSB values.…”
Section: Significancementioning
confidence: 99%
“…Others have questioned the accuracy of transcutaneous bilirubin (TcB) measurements, particularly in neonates with relatively high TSB. [12][13][14][15][16] The majority of studies of TcB have focused on hospitalized neonates prior to peak TSB values. If reliable TcB results could be demonstrated following discharge, when higher TSB values would be anticipated, this rapid, noninvasive, pointof-care technique would be attractive to parents and useful for providers who are implementing the AAP guidelines.…”
Section: Introductionmentioning
confidence: 99%